Regional control of histone H3 lysine 27 methylation in Neurospora - Jamieson, Kirsty (National Academy of Sciences, 2013)
Trimethylated lysine 27 on histone H3 (H3K27me3) is present in Drosophila, Arabidopsis, worms, and mammals, but is absent from yeasts that have been examined. We identified and analyzed H3K27me3 in the filamentous fungus Neurospora crassa and in other Neurospora species. H3K27me3 covers 6.8% of the N. crassa genome, encompassing 223 domains, including 774 genes, all of which are transcriptionally silent. N. crassa H3K27me3-marked genes are less conserved than unmarked genes and only ∼35% of genes marked by H3K27me3 in N. crassa are also H3K27me3-marked in Neurospora discreta and Neurospora tetrasperma. We found that three components of the Neurospora Polycomb repressive complex 2 (PRC2)—[Su-(var)3–9; E(z); Trithorax] (SET)-7, embryonic ectoderm development (EED), and SU(Z)12 (suppressor of zeste12)—are required for H3K27me3, whereas the fourth component, Neurospora protein 55 (an N. crassa homolog of p55/RbAp48), is critical for H3K27me3 only at subtelomeric domains. Loss of H3K27me3, caused by deletion of the gene encoding the catalytic PRC2 subunit, set-7, resulted in up-regulation of 130 genes, including genes in both H3K27me3-marked and unmarked regions.